Phosphorylation of the Nuclear Form of Varicella-Zoster Virus Immediate-Early Protein 63 by Casein Kinase II at Serine 186 - Mueller, Niklaus H. (American Society for Microbiology (ASM), 2009)
Varicella-zoster virus (VZV) open reading frame (ORF) 63 is abundantly transcribed in latently infected human ganglia and encodes a 278-amino-acid protein, IE63, with immediate-early kinetics. IE63 is expressed in the cytoplasm of neurons during VZV latency and in both the cytoplasm and the nucleus during productive infection; however, the mechanism(s) involved in IE63 nuclear import and retention has remained unclear. We constructed and identified a recombinant monoclonal antibody to detect a posttranslationally modified form of IE63. Analysis of a series of IE63 truncation and substitution mutants showed that amino acids 186 to 195 are required for antibody binding. Synthetic peptides corresponding to this region identified IE63 S186 as a target for casein kinase II phosphorylation. In addition, acidic charges supplied by E194 and E195 were required for antibody binding. Immunofluorescence analysis of VZV-infected MeWo cells using the recombinant monoclonal antibody detected IE63 exclusively in the nuclei of infected cells, indicating that casein kinase II phosphorylation of S186 occurs in the nucleus and possibly identifying an initial molecular event operative in VZV reactivation.